Diseño universal de aprendizaje y su impacto en el desarrollo cognitivo de los niños de 4 años de la Unidad Educativa “Francisco Huerta Rendón” - Cerezo Gualancañay, Angie Rosario (2023)
The Universal Design for Learning (UDL) is an educational approach that seeks to promote inclusion and equal opportunities for all students, regardless of their abilities, abilities or individual differences. The research was carried out with the purpose of identifying how this approach positively influences the cognitive development of children at this crucial stage of their development, finally, it was carried out using a mixed approach, combining qualitative and quantitative methods. In addition, an empirical study was carried out with observations in the classroom, a survey of teachers and parents, and the cognitive progress of the children was detailed through the observation sheet. The objective of this research is to determine the impact of the Universal Learning Design on the cognitive development of 4-year-old children, therefore, the results of the research demonstrated the positive impact of the DUA on strengthening memory, attention, language . and concentration of infants. Based on the results obtained, it is concluded that the Universal Learning Design is a valuable pedagogical tool to promote cognitive development from an early age. In conclusion, the importance of implementing inclusive and flexible approaches in educational practices is supported, in order to meet the diverse needs of children and promote their academic success.